2017
DOI: 10.1111/dom.13062
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic application of GPR119 ligands in metabolic disorders

Abstract: GPR119 belongs to the G protein-coupled receptor family and exhibits dual modes of action upon ligand-dependent activation: pancreatic secretion of insulin in a glucose-dependent manner and intestinal secretion of incretins. Hence, GPR119 has emerged as a promising target for treating type 2 diabetes mellitus without causing hypoglycaemia. However, despite continuous efforts by many major pharmaceutical companies, no synthetic GPR119 ligand has been approved as a new class of anti-diabetic agents thus far, nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 117 publications
0
36
0
Order By: Relevance
“…We then assessed the effect of OEA (endogenous GPR119 ligand) on proliferation of MCF-7 cells. Because EC 50 values of MBX-2982 and OEA for GPR119 are 3.9 nM and 0.2–5 μM, respectively [ 22 ], pharmacological potency of MBX-2982 is 51.3–1282.1 fold higher than OEA. When we assessed cell proliferation inhibitory effect of OEA (10 mM) in MCF-7 cells, the compound did not change the basal cell growth (Additional file 1 : Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then assessed the effect of OEA (endogenous GPR119 ligand) on proliferation of MCF-7 cells. Because EC 50 values of MBX-2982 and OEA for GPR119 are 3.9 nM and 0.2–5 μM, respectively [ 22 ], pharmacological potency of MBX-2982 is 51.3–1282.1 fold higher than OEA. When we assessed cell proliferation inhibitory effect of OEA (10 mM) in MCF-7 cells, the compound did not change the basal cell growth (Additional file 1 : Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that MBX-2982 activated AMP-activated protein kinase (AMPK), and pleiotrophic roles of AMPK have been investigated in many types of cancer [ 22 , 29 ]. Hence, we further investigated a potential role of AMPK in autophagy inhibition by GPR119 agonist.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Lauffer et al showed that OEA administration (10 μmol/L) stimulated GPR119, a G protein‐coupled receptor, in ileum L‐cells to secrete GLP‐1, a gut hormone that delays gastric emptying and exerts anorectic effects, in the mouse GLUTag cell line. Yang et al demonstrated that the activation of GPR119 induced the phosphorylation and activation of AMP‐activated protein kinase (AMPK) and thereby inhibited the expression of sterol regulatory element‐binding protein‐1 (SREBP‐1) in hepatocytes. The downregulation of SREBP‐1 decreased lipogenic enzyme gene expression, including acetyl‐CoA carboxylase (ACC), fatty acid synthase (FAS), and SCD1, resulting in a reduction in hepatic lipid accumulation …”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
“…GPR119 is considered part of the ECS . In patients with NAFLD, the hepatic expression of CB1R/CB2R and the serum levels of the endocannabinoid 2‐AG were increased .…”
Section: Major Mechanisms Of Action Of Oea In the Management Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation